Caught in the Whirlwind: How Will Pastoral Practitioners Respond? - Morgan, Jan (Pastoral psychology, 2025)
Climate change is a fundamentally a call for human change. What is being asked of us as pastoral practitioners in this new situation? This article reflects on this question through the lens of listening. Traditionally, we have listened primarily to other humans and/or the voice of the transcendent mediated through human channels. But these are not the only voices. Other-than-human voices—wind, water, fire, atmosphere, and non-human creatures—are now making their presences urgently felt. Earth herself is crying out. In response to this challenge, we attempted to re-imagine a traditional program of pastoral formation known as clinical pastoral education (CPE). To begin to listen to Earth’s voice involves a radical turning, a change of worldview and practices of attention. Reflection on a classic text (or theological reflection), a core component of the CPE process, played a critical role. In this article we listen to the classic wisdom text of the book of Job, particularly the astonishing speech of YHWH in chapters 38-39; provide an overview of the structural changes developed in CPE programs in eco-ministry; and trace the journey of one intern within one of these programs. This example shows the transformative outcomes that can occur when the core of pastoral care, empathic listening, is extended to the more-than-human world.